Robust Speed Control of Indirect Vector Controlled Induction Motors Using Neuro-Fuzzy Controllers - Dandil, Besir; Ata, Fikret (Gazi Univ, 2005)
This study proposes a robust speed control for the indirect vector controlled induction motors using neuro-fuzzy controller. Speed control performance of induction motors is affected from parameter deviations and nonlinearities in induction motor drives. The aim of the proposed control scheme is to improve the performance and robustness of the induction motor drives under nonlinear loads and parameter variations. Simulation results showing the speed control performance of NFC proposed for the induction motor drives are given for the different nonlinear loads and speed references.
Keywords: Neuro-Fuzzy Controller; induction motors; vector control; robust control; speed control